185k views
4 votes
What is the sum of (3x^2y+4xy^2-2y^3+3) and (x^2y+2y^3-4)

User Kospiotr
by
5.2k points

2 Answers

2 votes

Answer:

the sum is 4x^2y + 4xy^2 - 1

User Handrata Samsul
by
5.3k points
6 votes

Answer:

This is the sum ---> 4x^2y + 4xy^2 - 1

Explanation:

(3x^2y+4xy^2-2y^3+3) + (x^2y+2y^3-4)

(remove the parenthesis)

= 3x^2y + 4xy^2 - 2y^3 + 3 + x^2y + 2y^3 - 4

(now, group the like terms)

= -2y^3 + 2y^3 + 4xy^2 + 3x^2y + x^2y + 3 - 4

(add the elements you think are alike or similar)

= -2y^3 + 2y^3 + 4xy^2 + 4x^2y + 3 - 4

= 4xy^2 + 4x^2y + 3 - 4

= 4xy^2 + 4x^2y - 1

User Lomse
by
4.8k points